Colonial displacements and African coping strategies: The experience of BaTonga of Binga, Zimbabwe, 1956-2008 - Dhodho, Codelia Govha (Rhodes University, Faculty of Humanities, Department of History)
This study examines the challenges faced by BaTonga in livelihood reconstruction after involuntary displacement and resettlement from the Zambezi valley to pave way for the Kariba dam reservoir. It shows how they were forcibly evicted without compensation because of the racist policies of Southern Rhodesia. Their resettlement into an arid region infested with marauding elephants, malaria and tsetse fly undermined their complex livelihoods and eroded their self-sufficiency, but the study argues that they were active and resilient agents who adopted complex coping strategies. It shows how they had to adapt to dry-land farming and counter the effects of wildlife which plundered their crops and managed to secure the harvest in the drought-prone region. The study shows that although they adopted precarious livelihoods, they managed to survive under extreme circumstances for decades without any external assistance until the coming of NGOs who began to distribute free food from 1982. It argues that prolonged distribution of emergence food aid may not have been necessary, but its coming for almost three decades largely served political interests of both the NGOs and their governments. This perpetuated poverty as BaTonga also manipulated its distribution as a coping strategy against fragile livelihoods. This caused dependency which further plunged them into chronic food insecurity because they abandoned their traditional coping strategies. The study argues that both the colonial and postcolonial government as well as NGOs failed to address the root causes of livelihood insecurity in Binga for the five decades under study. It is therefore the contention of this study that the problem of food insecurity in Binga was not only an issue of recurring drought but was deeply rooted and pervasive due to multiple complex factors which made it difficult for the people to establish sustainable food production after displacement.
Keywords: Tonga (Zambezi people) -- Refugees; Subsistence farming -- Zambezi River Valley; Hunger -- Zambezi River Valley; Food security -- Zambezi River Valley; Adaptability (Psychology); Food relief -- Zambezi River Valley; Non-governmental organizations; Kariba Dam (Zambia and Zimbabwe)